Pengaruh Pengawasan, Disiplin Kerja Dan Penempatan Kerja Terhadap Kinerja Pegawai (Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Malang) - Fatkur Rohman; Hadi Sunaryo; M. Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conducted at the Agency for Human Resource Development and Human Resource Development (BKPSDM) Malang City. The purpose of this study was to examine and analyze the effect of supervision, work discipline and work placement on the performance of employees of the Malang Human Resources and Human Resources Development Agency (BKPSDM).The variables used are supervision, work discipline and work placement as independent variables, while the employee performance variable is the dependent variable. The sample used in this study was 44 employees, using quantitative methods. Data collection method by collecting primary and secondary data. The analysis used includes instrument testing, classical assumption test, normality test, multiple linear regression, hypothesis testing and coefficient of determination test using multiple regression analysis using SPSS 26 software for Windows. The results showed that the variables of work environment, work discipline and supervision had a simultaneous or partial effect on employee performance. Keywords: supervision, work discipline and work placement